Inflatable Tent For Covid-19 Isolation and Disaster Response With Independent Solar Energy - Budiyanto, Hery; Bonifacius, Nurhamdoko; Setiawan, Aries Boedi (Proceedings of International Conference of Graduate School on Sustainability, 2022)
This research departs from the problem of the lack of Covid-19 isolation rooms and disaster preparedness which currently uses a lot of tents with conventional structural systems and technology so inflatable tents are one of the right solutions. Electrical energy inflates inflatable tents and medical emergency equipment using solar power generation. The purpose of this study was to create and test an Inflatable Tent Prototype for the Covid-19 Isolation Post and Puskesmas. The research method used is experimental on an inflatable tent prototype with a solar power plantation; trials are carried out on variables: the strength of the tarpaulin, the speed of construction and dismantling, thermal comfort, and the effectiveness of the solar power plant. The results of the research are: the design and implementation of an inflatable tent prototype measuring 6x9 m2 for a capacity of 10 patients, a solar power plant with a power of 3,600 WP, and a 24 Volt 200 Ah VRLA battery capable of storing 4,800 watts of power, so that it is sufficient for electricity needs in an inflatable tent. Keywords: Covid-19, inflatable tent, isolation, disaster